KEINGINAN BUNUH DIRI DI KALANGAN REMAJA DAN SOLUSINYA DALAM IMAN KRISTEN - ERNAWATY TAMPUBOLON; Yanto Paulus Hermanto (The Way: Jurnal Teologi dan Kependidikan, 2022)
Suicide is often the last solution when a teenager feels that his life problems cannot be solved. Adolescents who cannot cope with their problems lead to prolonged stress and eventually depression to suicide. For this reason, this study is aimed at helping parties related to adolescents to provide a comprehensive understanding of suicide and its solutions. The research method used is a qualitative approach with a literature study method. The results and discussion in this study include the causes of suicidal ideation among adolescents and solutions to reduce suicidal ideation. The voices that appear in the minds of teenagers as a result of depression they are experiencing. The voice he heard was actually not real. The parties related to youth who need to gain this understanding are parents and the church. The conclusion of this study is that the causes of adolescents experiencing depression and even wanting to commit suicide are: Low self-esteem (bullying) and Loneliness, so it needs support from family and church to recover teenagers from depression and get closer to the Creator/improve spirituality, social interaction in the community, a more open personality, develop talents/favorites and others. Parents are expected to act as friends for teenagers, especially by applying authoritative parenting, being an example for teenagers, building Christ's character and family quality time. The church is expected to play a role in discipleship, cell community and Christian counseling. Keywords: Suicide; solution; depression; discipleship; cell community; counseling